Impact of flow on woodchip properties and subsidence in denitrifying bioreactors. Issue 1 (15th March 2021) - Schaefer, Abby; Werning, Kyle; Hoover, Natasha; Tschirner, Ulrike; Feyereisen, Gary; Moorman, Thomas B.; Howe, Adina C.; Soupir, Michelle L.
Abstract: Woodchip bioreactors are edge‐of‐field practices that remove nutrients from agricultural drainage water, with an effective lifespan estimated between 10 and 30 yr. Subsidence, or bioreactor settling and subsequent depression formation, is a concern of producers and stakeholders and little is known regarding its effect on bioreactor performance. Six woodchip bioreactors set at three different hydraulic residence times (HRTs 2, 8, and 16 h) were excavated after 2 yr of operation, with wood samples collected from multiple depths and distances from the bioreactor inlet. Subsidence was observed in all six bioreactors and was greater near the inlet. Particle‐size distribution did not change over the study period, indicating that smaller woodchips were not degrading preferentially or washing out of the bioreactor while the macropore space was simultaneously decreasing. Flow path analysis showed an increase in Morrill Dispersion Indices and short‐circuiting as well as decreases in drainable porosity and hydraulic efficiency; these changes were uniform across all three HRTs, suggesting that the decline in hydraulic properties was independent of flow. Further, despite increased woodchip decomposition as measured by C/N ratio in the 2‐h HRT bioreactors (mean ± SD = 64.9 ± 13.7) compared with the 8‐ and 16‐h HRT systems (90.3 ± 19.0, 95.6 ± 27.2, respectively), denitrification was still supported at all HRTs based on the results from a batch denitrification test. To offset wood aging, bioreactor fill material nearest the inlet could be replenished without excavation of the entire bioreactor.